Development and application of a fuzzy occupational health risk assessment model in the healthcare industry - Chalak, Mohammad Hossein; Kahani, Amin; Bahramiazar, Ghasem; Marashi, Zohreh; Popov, Tsvetan Ivanov; Dadipoor, Sakineh; Ahmadi, Omran (La Medicina del Lavoro, 2022)
Background: Hazards of the workplace and their impacts on the healthcare industry affect the quality of patient care and safety and impose high costs on the healthcare industry. Occupational health in this industry requires proper identification of hazards and managing the related risks. In this study, the researchers attempted to develop an easy-to-use and high applicability occupational health risk assessment model with a fuzzy approach to evaluate risks more precisely. Methods: In this study, a fuzzy inference system (FIS) was designed and applied to develop a risk assessment model. Conclusions: This study showed that the developed model could be applied as a practical model for evaluating occupational health risks. The weight of each risk criterion was used to calculate the risk level by adopting a fuzzy approach. The risk assessment results construed using the fuzzy set theory provided a broad picture of risks and could work adequately in the presence of inaccurate and insufficient data to calculate the risk. This model calculates risk levels and provides us with the dispersion and distribution of the calculated value of the risk number.